External Capabilities and the Limits to Social Policy - William A. Jackson (Critical Social Policy and the Capability Approach, 2014)
This chapter discusses the nature of external capabilities and how they bear upon social policy. Alternative definitions of external capabilities are compared and a simplified version suggested. It is argued that the issues surrounding external capabilities can be resolved only if the capability approach loses its individualistic slant by according higher status to social context. A layered, non reductionist social theory would be helpful here, and a layered scheme for the capability approach is suggested. Such a scheme can show up the narrowness of traditional social policy and its muted impact on external capabilities. Despite endeavouring to fight poverty, social policy cannot guarantee the benign external conditions under which a person's lifetime opportunities will flourish.
Keywords: I31; I32; I38; Z13; Z18; 320; capabilities; capability approach; welfare; social policy